Comparative Study of Natural Tourism in Cirebon Regency and Banyumas Regency - Syaeful Bakhri (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
Cirebon Regency has complete geography, there are coastlines, and hills in the south, bordering Majalengka and Kuningan Regencies. The strategic condition is equipped with access to 2 toll exit doors. With these conditions, the accessibility of Cirebon Regency is very open to the development of natural tourism. Meanwhile, Banyumas Regency, which does not have a coastline, can attract tourists to come, especially visiting nature tourism. This research uses mixed methods. Qualitative analysis was conducted to find policy priorities in the development of natural tourism, and quantitative analysis was used to examine the effect of tourism-supporting conditions on the potential for natural tourism development and to conduct comparative studies between Cirebon and Banyumas regencies. The results of the Process Hierarchy Analysis (AHP) show that the variables with the main priorities are Accessibility, the Role of Local Government, and Road Infrastructure. The results of the regression and correlation analysis showed that the supporting conditions of tourism influenced the potential for tourism development. T-test analysis that compares the perception of the people of Banyumas Regency (13%) Higher than the people of Cirebon Regency (10%) on the potential for developing nature tourism. With the results of this analysis, several things can be recommended regarding the development of the potential for nature tourism in Cirebon Regency, including; (1) Ease of accessibility to the location of natural tourism sites (2) improvement of infrastructure, especially roads to natural tourism sites and (3) strengthening the role of local governments in the development of natural tourism in Cirebon Regency.Keywords: Nature Tourism, Comparison, Cirebon Regency